Diagnosis dan Tata Laksana Thyroid Storm yang Dipicu oleh Perikarditis Akut - Ida Bagus Aditya Nugraha; LP Dea Sasmita P; Wira Gotera (MEDICINUS, 2024)
Thyroid storm is a life-threatening condition that requires prompt diagnosis and emergency treatment. This condition manifests as multiple organ decompensation characterized by loss of consciousness, high fever, heart failure, diarrhea,and jaundice. We report a case of a 51-year-old man with a chief complaint of fever that has been felt since the night before admission. Body temperature was up to 38°C and started while he was resting. Patient also reported dry, intense cough, since five days ago, accompanied with shortness of breath when lying down. The patient also felt palpitations sincethe previous night and still felt until the morning of admission, and did not improve with rest. The patient was diagnosed by observation of suspension shock due to cardiogenic shock, suspect Graves’ disease (thyroid storm), ADHF profileB et causa suspect CAD, AF RVR, type 2 DM, myofascial pain syndrome with differential diagnosis: headache related toinfection, hyponatremia chronic asymptomatic hypoosmolar hypervolemic et causa suspect dilution, hypoalbuminemia etcausa suspect chronic inflammation, and upper respiratory tract infection. Thyroid storm cases require a multidisciplinaryapproach in terms of diagnosis and therapy. In this case, the patient is referred to the internal medicine, cardiac, andneurology departments.